2019
DOI: 10.1002/ijc.32274
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytosis and neutrophilia as independent prognostic immunological biomarkers for clinical outcome in the CAO/ARO/AIO‐04 randomized phase 3 rectal cancer trial

Abstract: Peripheral blood leukocytosis and neutrophilia reflect cancer inflammation and have been proposed as prognostic immunological biomarkers in various malignancies. However, previous studies were limited by their retrospective nature and small patient numbers. Baseline peripheral blood leukocytes, neutrophils, hemoglobin, platelets, lactate dehydrogenase and carcinoembryonic antigen (CEA) were correlated with clinicopathologic characteristics, and clinical outcome in 1236 patients with rectal cancer treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Liu et al found an association between absolute number of systemic lymphocytes and pathologic response; furthermore, they showed that a higher peripheral lymphocyte count was associated with a higher infiltration of CD4+ and CD8+ cells into the tumor [18]. Likewise, an effective local or systemic treatment of tumors leads to a decline of systemic inflammatory markers, so that a link between tumor mass and the degree of systemic inflammatory response, which our data emphasize, seems reasonable [19,29,30,31,32]. The knowledge of this association is important for the interpretation of the study results and the design of translational studies that investigate the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 53%
“…Liu et al found an association between absolute number of systemic lymphocytes and pathologic response; furthermore, they showed that a higher peripheral lymphocyte count was associated with a higher infiltration of CD4+ and CD8+ cells into the tumor [18]. Likewise, an effective local or systemic treatment of tumors leads to a decline of systemic inflammatory markers, so that a link between tumor mass and the degree of systemic inflammatory response, which our data emphasize, seems reasonable [19,29,30,31,32]. The knowledge of this association is important for the interpretation of the study results and the design of translational studies that investigate the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 53%
“…Until now, only few studies concerned the issues about how were the inflammatory markers changed, and what were the impacts of the changes on the prognosis. According to the study [22] related to rectal cancer, the treatment-induced leukopenia correlated with a favorable OS; however, when it came to Lym, there was contradictory result reported [23]. Another study [24] related to gastric cancer revealed that the NACT had different effects on Lym depending on the subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are major inflammatory constituents of TME, which can facilitate the growth and development of tumor by different mechanisms (24,25). Diefenhardt et al (26) found that leukocytosis and neutrophilia tended to predict the poor clinical outcome. Meanwhile, the variation of lymphocytes often related to virus infection, as the center of immune response.…”
Section: Discussionmentioning
confidence: 99%